Histamine2-Receptor Antagonists, Proton Pump Inhibitors, or Potassium-Competitive Acid Blockers Preventing Delayed Bleeding After Endoscopic Submucosal Dissection: A Meta-Analysis - Jiang, Xin; Li, Jiahao; Xie, Jingmei; Liang, Zhuoru; Wan, Ning; Jiang, Jie; Zhang, Tiantian; Wu, Yingyu (Frontiers in Pharmacology, 2019)
Background: Endoscopic submucosal dissection (ESD) was commonly used for en bloc resection in gastric cancer and adenoma with the risk of delayed bleeding after ESD. We conducted a direct and indirect comparison meta-analysis to evaluate the best choice in preventing post-ESD bleeding among proton pump inhibitors (PPIs), histamine2-receptor antagonists (H2RAs), and the most widely used potassium-competitive acid blocker (P-CAB), vonoprazan. Methods: The Pubmed, Cochrane Library, and Embase were searched for randomized trials. We pooled odds ratios (OR) for preventing post-ESD bleeding using meta-analysis. Results: Sixteen randomized trials met the inclusion criteria including 2062 patients. Direct comparisons showed slightly significant efficacy in PPIs rather than H2RAs in preventing post-ESD bleeding (OR: 1.83; 95% CI: 1.10 to 3.05) and vonoprazan was better than PPIs (OR: 0.46; 95% CI: 0.25 to 0.86). The adjusted indirect comparison indicated vonoprazan was superior to H2RAs (OR: 0.30, 95% CI: 0.12 to 0.74). In subgroup analysis, PPIs had similar efficacy as H2RAs in 4 weeks while PPIs were better than H2RAs in 8 weeks treatment (OR: 1.91; 95% CI: 1.08 to 3.40). The superiority of vonoprazan than PPIs was more significant in combination therapy (OR: 0.18; 95% CI: 0.04 to 0.69). There was a significant difference in vonoprazan for 8 weeks of medication (OR: 0.44; 95% CI: 0.21 to 0.92). Conclusions: The effects of vonoprazan is better than PPIs than H2RAs in preventing bleeding after ESD. When vonoprazan combined with mucosal protective antiulcer drug in treatment or used in eight weeks of medication, the efficacy may be even better